Programmed Death Ligand 1 expression in Urothelial Carcinoma.A retrospective study in Duhok City-Iraq. - Zuzan Shawkat Mustafa; Gina James Keorges; Alaa Hani Raziq (Advanced Medical Journal)
Background and objective: Programmed death ligand-1 protein expression has been linked to the severity of Urothelial cancer. The objectives of this study were to evaluate the expression of programmed death-ligand 1 and determine the association with tumour grade, stage, type (Papillary and non papillary), muscle invasion, age, and gender.